2005
DOI: 10.1111/j.1440-1746.2005.03932.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors for delirium tremens in alcohol dependence

Abstract: A simple assessment using the past history of DT and the pulse rate, which may be easily evaluated in clinical settings, can allow physicians to readily identify the patients who are at a high risk of developing DT during an alcohol dependence period and reserve more intensive therapies for the selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 25 publications
(29 reference statements)
3
85
3
1
Order By: Relevance
“…6,7,10 . Two studies are retrospective, utilize hospitalized medical patients, and have conflicting results.…”
Section: Protocol Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,10 . Two studies are retrospective, utilize hospitalized medical patients, and have conflicting results.…”
Section: Protocol Developmentmentioning
confidence: 99%
“…In the second study, 33 % of patients developed DTs; HR> 100 and a history of prior DTs were the strongest predictor variables. 7 The one identified prospective study examined risk factors for DTs among patients requesting alcohol detoxification. 10 Of these patients, 43.5 % had prior DTs and 41.6 % had prior seizures.…”
Section: Protocol Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reviews showed the expectation of experiencing withdrawal delirium to be 4-15% for alcoholdependent individuals 21,22 . Delirium develops in 5-20% of patients treated for alcohol withdrawal syndrome 10,11,23,24 , with the rates varying from study to study from 1.25% to 33%.…”
Section: Prevalencementioning
confidence: 99%
“…Without proper management, mortality may range from 5% to 15% or even 20% (ref. 23,39 ). When treated appropriately (benzodiazepines) and detected early, the mortality should not exceed 1% (ref.…”
Section: Complications Of Delirium Tremensmentioning
confidence: 99%